2007
DOI: 10.1097/mlg.0b013e318041f70c
|View full text |Cite
|
Sign up to set email alerts
|

Stroboscopy Versus High‐Speed Glottography: A Comparative Study

Abstract: Regardless of the method used (VS or HGG), perceptive evaluations of vibratory movements of vocal folds revealed a higher variability than assumed. This result supports the need for objective methods to analyze vocal fold vibratory movements. Therefore, real-time imaging of vocal fold vibratory movements using HGG will be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 8 publications
1
35
0
2
Order By: Relevance
“…HSV captures vocal fold dynamics in real time and is suited for a quantitative analysis. Because of its objective nature, HSV is proven to be more reliable than stroboscopy (19). Supplemented with appropriate computerized analysis procedures HSV allows for the detection of even slight disturbances of vocal folds (20).…”
Section: Introductionmentioning
confidence: 99%
“…HSV captures vocal fold dynamics in real time and is suited for a quantitative analysis. Because of its objective nature, HSV is proven to be more reliable than stroboscopy (19). Supplemented with appropriate computerized analysis procedures HSV allows for the detection of even slight disturbances of vocal folds (20).…”
Section: Introductionmentioning
confidence: 99%
“…Olthoff et al noted that while HSI was more reliable and less prone to interpretive variances than stroboscopy, their comparative study was unable to demonstrate any specific clinical scenarios in which HSI is clearly indicated. 11 Patel et al found HSI a useful adjunct to stroboscopy specifically with neuromuscular etiologies of dysphonia; however, it is unclear as to what extent clinical diagnosis and treatment would differ without HSI. 10 Mortensen and Woo described a single case report in which HSI did change the clinical course of a dysphonia patient.…”
Section: Discussionmentioning
confidence: 99%
“…Because HSI video clips did not include sound files, sound was removed from the stroboscopy videos as has been performed in previous studies. 11 Examination videos were de-identified, coded, and randomized. The videos were then uploaded to an online rating platform (http://www.classmarker.com; ClassMarker Pty Ltd., Sydney, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…Adicionalmente, la variabilidad entre examinadores en ambos tipos de examen es alta, por lo que se hace necesario trabajar en la búsqueda de métodos objetivos para el análisis de la actividad vibratoria (10,11).…”
Section: A Laringoscopia De Alta Velocidad Y Videoquimografíaunclassified